Perbedaan Mutu Pelayanan Kesehatan Terhadap Puskesmas Terakreditasi Puskesmas Dan Puskesmas Tidak Terakreditasi Di Kabupaten Kolaka Utara Tahun 2021 - Kasmiati Putri; Muhammad Rifai; Andi Yusuf (NERSMID : Jurnal Keperawatan dan Kebidanan, 2022)
Accreditation is an acknowledgment given by an independent institution that administers the accreditation which is determined after meeting the accreditation standards. The purpose of the study was to determine the difference in the quality of health services to accredited and unaccredited health centers. This research was carried out in North Kolaka Regency. The type of research that will be used is quantitative research with a comparative approach, which is to compare two groups with certain variables. The results showed that the average quality of health services in accredited health centers was 85.17, with a standard deviation of 6,304, a minimum value of 70 and a maximum value of 94, the average quality of health services in unaccredited health centers was 66.65, with a standard deviation deviation of 5.252, a minimum value of 56 and a maximum value of 79 and there is a difference in the quality of health services for accredited health centers and unaccredited health centers with a value of = 0.000 where < (α = 0.05) in North Kolaka Regency in 2021. Suggestions in research are that it can become information material for puskesmas to be able to improve the quality of health services provided to be even better, can be additional reading in the library and is expected to add insight to readers, especially regarding accreditation and quality of health services at health centers and can provide useful information to increase knowledge and encourage and help further research in terms of developing research methods.